Genotoxin Effect of Composite Resin - Septiwidyati, Tienneke Riana; Auerkari, Elza Ibrahim (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 9 No 1 (2019): Indonesian Journal Of Legal And Forensic SciencesDO - 10.24843/IJLFS.2019.v09.i01.p02, 2019)
At this moment composite resin is the most widely used material for dental restoration. The content of the resin is a mixture of monomer bisphenol A glycidyl methacrylate (Bis-GMA), trimethylene glycol dimethylmethacrylate (TEGDMA) and urethane dimethacrylate (UDMA) and special particle fillers made of radioopaque glass. Many studies have been conducted to study the biocompatibility of composite resin, especially the cytotoxicity and genotoxicity test. Genotoxicity tests that are often carried out are comet test for DNA damage protection and micronuclei test for protection of genome damage. The monomer content of composite resins can have a genotoxic effect.